PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN GRAB DI KOTA BATAM - Winata, Windy; Evyanto, Winda (LPPM Universitas Putera Batam, 2021)
The study aims to examine and analyze the effect of service quality, trust and customer satisfaction on Grab customer loyalty in Batam City. The variabels in this study are variable service quality (X1), trust (X2), customer satisfaction (X3) on customer loyalty (Y) Grab in Batam City. The technique of collecting data with a questionnaire. A sample of 100 respondents who came from the community who used Grab in Nagoya, Batam City and using purposive sampling technique. The effect test in this study is a statistical analysis method consisting of multiple linear regression test. The result of the analysis state that the variable service quality has a significant effect on the customer loyalty variable with t count 2,014 > t table 1,988, trust variable has a significant effect on customer loyalty variable with t count 2,431 > 1,988 and customer satisfaction has a significant effect on customer loyalty variable with t count 3,412 > t table 1,988.